2011
DOI: 10.1289/ehp.1002321
|View full text |Cite
|
Sign up to set email alerts
|

Intellectual Impairment in School-Age Children Exposed to Manganese from Drinking Water

Abstract: BackgroundManganese is an essential nutrient, but in excess it can be a potent neurotoxicant. Despite the common occurrence of manganese in groundwater, the risks associated with this source of exposure are largely unknown.ObjectivesOur first aim was to assess the relations between exposure to manganese from drinking water and children’s intelligence quotient (IQ). Second, we examined the relations between manganese exposures from water consumption and from the diet with children’s hair manganese concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
409
5
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 537 publications
(434 citation statements)
references
References 38 publications
15
409
5
5
Order By: Relevance
“…For example, studies in Bangladesh suggest that ingesting high doses of Mn in drinking water is associated with neurotoxic effects in children, interfering with their intellectual function, as well as causing infant mortality 24,25 . Similar studies have shown that drinking water containing much lower concentrations of Mn than those found in Bangladesh also caused intellectual impairment in school children 26 . The environmental exposure to Mn from industrial and mining sources, and negative cognitive performance of children were also reported 27,28 .…”
Section: Introductionmentioning
confidence: 65%
“…For example, studies in Bangladesh suggest that ingesting high doses of Mn in drinking water is associated with neurotoxic effects in children, interfering with their intellectual function, as well as causing infant mortality 24,25 . Similar studies have shown that drinking water containing much lower concentrations of Mn than those found in Bangladesh also caused intellectual impairment in school children 26 . The environmental exposure to Mn from industrial and mining sources, and negative cognitive performance of children were also reported 27,28 .…”
Section: Introductionmentioning
confidence: 65%
“…Intravenous administration or inhalation of manganese causes manganese deposition in the brain, but the oral intake of manganese rarely results in manganese deposition. Intellectual impairment in children after excess oral intake of manganese has been reported, albeit without histological proof [30]. Most orally ingested manganese does not remain in the human body, due to several mechanisms.…”
Section: Manganesementioning
confidence: 99%
“…Mercury poisoning is manifested by irritability, poor concentration, memory deficiencies, anxiety, and depression [58][59]. Moreover, lead and manganese have also induced cognitive and behavioral deficits in different population groups with higher exposure levels [60][61][62][63]. These metals can differ in their neurological effects, but they both disrupt presynaptic neurotransmission [64].…”
Section: Heavy Metals: Neuroendocrine Disruptions and Obesitymentioning
confidence: 99%